PERANCANGAN HOTEL RESORT DI PULAU LAKI KEPULAUAN SERIBU JAKARTA DENGAN PENERAPAN ARSITEKTUR TROPIS MODERN - Muhammad Herdyana Zaeny; Sri Kurniasih; Karya Subagya (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2021)
This Resort Hotel on Laki Island, Seribu Islands is designed to provide accommodation facilities for tourists which also provide beach-style tourism and recreation facilities that support archipelagic tourism and other supporting facilities. The application of Modern Tropical Architecture was chosen because of the mass formation and site circulation which is designed to describe the characteristics of island tourism activities into the building structure. This makes the appearance of the building more expressive and has character following the function of the building as a resort hotel. Tourism is a sector with great potential to increase the country's foreign exchange. One of the places with natural beauty that can develop the tourism sector is Laki Island. Laki Island is an island with white sandy lowlands and is overgrown with trees, mangrove trees, ketapang trees, wind wood and waru trees on the beach. Therefore, a tourist spot needs to be supported by the existence of accommodation facilities in the form of a resort hotel, given its location which is quite far from the city and it is not possible to visit and enjoy all tourist attractions in just one day.